Tp-Te interval prolongs in hypertension independent of the left ventricular geometry - Özbek, Sinan Cemgil (Journal of Surgery and Medicine, 2021)
Background/Aim: Hypertension (HT) may modulate left ventricular (LV) geometry. Electrocardiographic Tp-Te, QT and QTc interval, and Tp-Te/QTc ratio are among the parameters of ventricular repolarization (VR) that may predict ventricular arrhytmogenic potential and possess prognostic significance. It is well known that left ventricular hypertrophy is associated with increase in the parameters of VR; however, little is known about the association of these parameters with other forms of LV geometry in HT. Our aim was to assess this association. Methods: A total of 162 newly diagnosed essential HT patients were enrolled and divided into those with concentric LV remodeling (n=79) and those with normal LV geometry (n=83). Healthy normotensive subjects (n=76) comprised the control group. Data were gathered retrospectively from electrocardiographic, echocardiographic, and demographic records. Results: QT interval, P-wave duration, and QRS duration were similar among the 3 groups (P>0.05). Tp-Te, QTc and Tp-Te/QTc were greater in the HT group compared with the controls (P<0.001). In a pair-wise comparison between 2 HT subgroups, these parameters were similar (P>0.05). There was no correlation between Tp-Te interval, LV mass and LV mass index among the study population. Conclusion: Tp-Te may be useful in prognostic stratification of HT. Regardless of the LV geometry, HT patients have prolonged Tp-Te and QTc intervals, and increased Tp-Te/QTc ratio compared to the healthy subjects. Our findings may suggest possible utilization of Tp-Te as HT-related end-organ damage in the future.